Association between MIF gene variation and Meniere's disease. (8th April 2013) - Yazdani, N.; Khorsandi Ashtiani, M. T.; Zarandy, M. M.; Mohammadi, S. J.; Ghazavi, H.; Mahrampour, E.; Amiri, P.; Amoli, M. M.
Summary Several pieces of evidence support the involvement of immune system in Menière's disease (MD). Macrophage migration inhibitory factor (MIF) plays a key role in immune‐mediated reactions. Several studies have shown an association between MIF gene polymorphisms and susceptibility to various inflammatory and autoimmune disorders. The aim of this study was to explore the association between MIF‐173 G/C polymorphism and MD in an Iranian population. In this case–control association study, MD cases (N = 72) were recruited and were comprised of definitive MD (N = 58) and probable MD (N = 14) subjects. Normal healthy subjects (N = 100) were also included. Genotyping for MIF‐173 G/C polymorphism was carried out using PCR‐RFLP technique. There was a significant increase in genotype GG in patients with MD compared with the control group. (GG vs. GC + CC, P = 0.02, OR = 2.08, 95% CI: 1.02–4.3). This was more significant when definitive MD was stratified and compared with the controls (GG vs. GC + CC, P = 0.009, OR = 2.6, 95% CI = 1.19–6.18). This study's result indicates the potential role of MIF in MD of which further evaluation is required. Also, the more significant association between MIF gene polymorphism and definitive MD designates the involvement of specific pathogenic mechanisms which may be considered as a marker for diagnosis.